2004
DOI: 10.1016/j.jhsb.2004.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium Enhanced Mr Assessment of Proximal Fragment Vascularity in Nonunions after Scaphoid Fracture: Does It Predict the Outcome of Reconstructive Surgery?

Abstract: This study investigated whether the outcome of bone graft and internal fixation surgery for nonunion of scaphoid fractures could be predicted by gadolinium-enhanced MR assessments of proximal fragment vascularity. Sixteen established scaphoid fracture nonunions underwent gadolinium-enhanced MR scanning before surgical treatment with bone grafting and internal fixation. No relationship was found between MR enhancement and the outcome of surgery. Union was achieved in eight of the 12 nonunions with more than 50%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
7

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 12 publications
2
38
0
7
Order By: Relevance
“…There are contradictory data about the accuracy of assessment of scaphoid viability with use of static contrast material-enhanced magnetic resonance (MR) imaging. Although some investigators have postulated good correlation between preoperative imaging fi ndings and postoperative union rates ( 9,10 ), others have demonstrated that MR imaging fi ndings are not predictive of reconstructive success ( 11,12 ).…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are contradictory data about the accuracy of assessment of scaphoid viability with use of static contrast material-enhanced magnetic resonance (MR) imaging. Although some investigators have postulated good correlation between preoperative imaging fi ndings and postoperative union rates ( 9,10 ), others have demonstrated that MR imaging fi ndings are not predictive of reconstructive success ( 11,12 ).…”
Section: Patientsmentioning
confidence: 99%
“…In addition, the area of gadolinium uptake was judged on a semiquantitative scale ( 9,12 ), as follows: 4 = 80%-100% of fragment, 3 = 50%-79% of fragment, 2 = 20%-49% of fragment, and 1 = less than 20% of fragment. Finally, readers were asked to rate the viability of the proximal scaphoid pole with use of a fi ve-point Likert scale, where 1 = defi nitely viable, 2 = probably viable, 3 = indeterminate, 4 = probably nonviable, and 5 = defi nitely nonviable.…”
Section: Standard Of Referencementioning
confidence: 99%
“…This is similar to our findings with pedicle screws in spinal fractures. Singh et al 12 used gadolinium-enhanced fat-suppressed sequences in the assessment of scaphoid fractures, particularly looking at vascularity and avascular necrosis; the additional benefit of gadolinium is not established but may be an area for further investigation in spinal fractures. The change in signal characteristics with time in vertebral compression fractures has been described by Sung et al 13 This shows T1-w hypointensity and T2-w hyperintensity in compression fractures o1 month old with signal returning to normal by 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have demonstrated a strong correlation with the vascular status at surgery [6][7][8][9][10]; however, others have concluded the opposite [11]. Disparate conclusions have also been reported regarding the usefulness of gadolinium-enhanced MRI to evaluate proximal pole vascularity, even when dynamic imaging was used [11][12][13]. The issue is further complicated by a report describing the Bapparent increased contrast pattern^in 6 of 13 patients with surgically proven avascular proximal poles [14].…”
Section: Introductionmentioning
confidence: 99%
“…The issue is further complicated by a report describing the Bapparent increased contrast pattern^in 6 of 13 patients with surgically proven avascular proximal poles [14]. To our knowledge, only four articles have attempted to correlate surgical outcome and the preoperative MRI findings, two analyzing nonvascularized bone grafts, one analyzing vascularized bone grafts, and one analyzing both vascularized and nonvascularized grafts, [11,12,15,16].…”
Section: Introductionmentioning
confidence: 99%